Fiction e identità narrativa (ENTHYMEMA, 2012)
In this article we offer a survey of the main approaches of theory of the novel, which interpret this narrative genre as a form of unveiing of the inner life. By comparing these theories to the concept of “narrative identity”, as developed by Ricœur, we offer here a new idea of analysis of inner lives narrated in fictional works. Our starting point will be Auerbach’s definition of “modern realism” as an attempt to approach objective reality through “numerous subjective impressions received by various individuals”.